Alternatives to Traditional Language Sample Measures With Emergent Bilingual Preschoolers. Issue 2 (April 2020) - Guiberson, Mark
Abstract : The aim of this article was to evaluate the use of alternatives to traditional language sample analysis (LSA) measures with bilingual preschool-aged children. A database of 184 bilingual preschool children, including children with developmental language disorder (DLD), was used in this study. The goals of the study were to establish the convergent validity between traditional language sample measures and alternative measures of clinician-observed and parent-reported longest utterance, compare groups across traditional and alternative measures, and establish to what extent alternative measures predict language status (typical or DLD). Results indicated that alternative measures may be useful in describing the language of preschool bilingual children, but none of the measures alone would provide adequate diagnostic information to make a determination of DLD status.